2006
DOI: 10.4325/seikeikakou.18.883
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Bowing Phenomenon for Polyimide Film Accompanying Reactions and Removal of Solvents During Film Heating with Tenter

Abstract: In this report, the bowing behavior and the state of stress in PI film during tenter heating process were predicted by a finite element method (FEM). In the FEM analysis, the authors focused especially on the first zone of tenter heating where the shrinking stress and changes in film hardness arise resulting from removal of residual solvents and chemical reaction (imidation). The analysis was carried out under the assumption that the PI film in the tenter heating was linearelastic. From the orientation measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…They obtained good agreement between the simulated and the experimental results. Itoh et al [32] have predicted the bowing phenomenon and the state of stress during reaction and removal of the solvents process in the tenter for polyimide (PI) film using FEM under the assumption that PI film is a linear‐elastic body. They have reported that the experimental orientation angle of the film was comparatively close to the direction of the maximum principal stress calculated by FEM.…”
Section: Introductionmentioning
confidence: 99%
“…They obtained good agreement between the simulated and the experimental results. Itoh et al [32] have predicted the bowing phenomenon and the state of stress during reaction and removal of the solvents process in the tenter for polyimide (PI) film using FEM under the assumption that PI film is a linear‐elastic body. They have reported that the experimental orientation angle of the film was comparatively close to the direction of the maximum principal stress calculated by FEM.…”
Section: Introductionmentioning
confidence: 99%